MEDIASI PENAL: ALTERNATIFf PENYELESAIAN PERKARA KDRT - Ludfi Ludfi; Jumati Jumiati; Febriana Hidayati (Fakultas Syariah dan hukum Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
AbstractSettlement of domestic violence cases in Indonesia still uses the retributive justice approach, the settlement of these cases is solely intended to impose sanctions on perpetrators of domestic violence without considering the loss suffered by the victim. Therefore, Law Number 23 of 2004 concerning Elimination of Domestic Violence regulates the rights of victims in obtaining justice through the criminal justice system so that the aim is not only to take action against perpetrators but also protect victims of domestic violence.Further, Government Regulation Number 4 of 2006 concerning the Implementation and Cooperation of the Recovery of Victims of Domestic Violence intersects with the concept of restorative justice. This can be seen by the regulation of the recovery of victims of domestic violence involving collaboration with various parties. However, when compared, it is still considered not enough to provide protection and recover victims of domestic violence, because only one goal is set from restorative justice, the recovery of victims. This regulation still puts victims as objects by putting the victims away to participate in the criminal justice system, and not explaining the recovery process, which is the ultimate goal of restorative justice.